The Relationship Between Mother's Level of Knowledge and Attitude Towards Exclusive Breastfeeding - Adriati, Febri; Hidayati, Rizka Dita (Universitas Islam Lamongan, 2024)
Abstract In Indonesia, the percentage of mothers providing exclusive breastfeeding is 69.7%. This figure has surpassed the national target of 45% in the performance report of the Ministry of Health for 2020–2021. However, it is still considered a standard figure compared to the Ministry of Health's strategic plan target for the 2020–2024 period, which is 69%. The benefits of exclusive breastfeeding can protect infants from gastrointestinal infections, which can lead to severe malnutrition, one of which is stunting. The purpose of this study is to determine the relationship between mothers' knowledge and attitudes toward exclusive breastfeeding at Karisma Maternity Clinic, Panjang, Bandar Lampung. This study is an analytical survey with a cross-sectional study design, conducted at Karisma Maternity Clinic, Panjang, Bandar Lampung, in September 2024. The results of this study indicate a relationship between mothers' knowledge and attitudes and the provision of exclusive breastfeeding at Karisma Clinic, Panjang, Bandar Lampung. Keywords: Knowledge, Attitude, Exclusive Breastfeeding, Breastfeeding Mothers, Newborn